Оцінка рівня ліквідності балансу за даними фінансової звітності сільськогосподарських підприємств - Ульянченко, Наталія Володимирівна (Мелітопольська типографія "Люкс", 2016)
У статті досліджено дискусійні питання категорії "ліквідність підприємства" та виявлено, що ліквідність підприємства часто ототожнюють з платоспроможністю, з ліквідністю балансу, з ліквідністю активів, що може обмежувати економічний зміст даного поняття. В роботі також проведено аналіз рівня ліквідності балансу сільськогосподарських підприємств в залежності від співвідношення власних та залучених коштів.

Financial standing is the most important characteristic of an enterprise economic activity. It determines the competitiveness of the enterprise and its potential of business cooperation, it is a pillar of effective implementation of economic interests of all units participating in financial relations, the enterprise itself and its partners. Estimation of enterprises’ financial standing reliability has become urgent nowadays. It can be explained by many factors, primarily the economic crises and increasing amount of enterprises which are on the verge of bankruptcy. The article describes the issue of “enterprise liquidity” and it was found that enterprise liquidity is often identified with financial responsibility, accounting liquidity, asset liquidity. That can constrain the economic sense of this concept. Based on the analysis of the determined approaches we have defined the enterprise liquidity as the ability of the enterprise to convert its assets into money in order to pay matured bills as quickly as possible. We have also analyzed the accounting liquidity level of agricultural enterprises considering the proportion of owned assets and outside funds. In result, it was discovered that the proportion of owned assets and outside funds is one of the prominent factors of agricultural enterprises’ accounting liquidity. In addition, analysis of the liquidity of the enterprises in the dynamics revealed that most of farm finances its operations only at their own expense. In the period under virtually stopped lending long-term. Therefore, public policy should aim to reduce the cost of credit.
Liquidity level estimation according to financial accounting at agricultural enterprises
Keywords: власні кошти; економічна діяльність; залучені кошти; фінанси; бізнес; підприємницька діяльність; платоспроможність; конкурентоспроможність; financial reporting; liquidity; own funds; borrowed funds; efficiency; agricultural enterprises